PEMANFAATAN EKSTRAK BUNGA KECOMBRANG (ETLINGERA ELATIOR) SEBAGAI ALTERNATIF BAHAN SURFAKTAN DETERGEN GUNA MEMAKSIMALKAN POTENSI TUMBUHAN LOKAL SUMATRA UTARA - Dakwan Soaloon Harahap; Teguh Parmonangan Hasibuan; Syawaluddin Nasution; Muhammad Doni Anggara; Reza Faisal (Jurnal Media Akademik (JMA), 2024)
Detergent is a chemical compound used to wash clothes. Unfortunately, detergents contain the dangerous substance LAS (Linear Alkylbenzene Sulfonate). Detergent waste containing LAS can pollute rivers, thereby hampering Sustainable Development Goal number 6, namely clean water and sanitation, even though many Indonesians still use river water as a source of clean water. Therefore, an environmentally friendly substitute for LAS is needed, such as the saponin contained in the kecombrang plant, which is a local plant from North Sumatra. Saponin is a nonionic surfactant and has the potential to be used as a cleaning agent. From the formulation of the problem, the objectives of this research are: 1) to find out liquid detergent formulations that are environmentally friendly and in accordance with SNI 06-4075-1996 by minimizing the use of LAS and replacing it with kecombrang flower extract from North Sumatra; 2) prove the potential for the saponin content in kecombrang flowers from North Sumatra to be an ingredient in making liquid detergent that can replace LAS. The research uses quantitative analysis chemical methods, namely carrying out formulations in making detergent products. There are four detergent formulations with varying ratios of kecombrang flower extract and LAS of 1:1 (formula 1), 2:1 (formula 2), 3:0 (formula 3), and 0:3 (control formula). Research stages: 1) extraction of kecombrang flowers; 2) making detergent; 3) testing saponins in combrang extract; 4) detergent quality testing. The research results show that formula 1 is recommended as the best formula because it has a pH value of 11.7; specific gravity 0.99 g/ml; as well as organoleptic test results (homogeneous shape, color and distinctive odor) which are in accordance with SNI (Indonesian National Standardization). Combrang extract has also been proven to contain saponin which forms foam, thereby increasing the detergency power of detergent.